Foreign Aid and Real Exchange Rate Adjustments in a Financially Constrained Dependent Economy - Turnovsky, Stephen; Cerra, Valerie; Tekin, Serpil (Washington, D.C. : International Monetary Fund, 2008)
A dynamic dependent-economy model is developed to investigate the role of the real exchange rate in determining the effects of foreign aid. If capital is perfectly mobile between sectors, untied aid has no longrun impact on the real exchange rate. A decline in the traded sector occurs because aid, being denominated in traded output, substitutes for exports in financing imports. While untied aid causes short-run real exchange appreciation, this response is very temporary and negligibly small. Tied aid, by influencing sectoral productivity, does generate permanent relative price effects. The analysis, which employs extensive numerical simulations, emphasizes the tradeoffs between real exchange adjustments, long-run capital accumulation, and economic welfare, associated with alternative forms of foreign aid.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet